FIBER QUALITY-COLOR ASSOCIATIONS IN GOSSYPIUM HIRSUTUM L. HYBRIDS - Babamuradovna, Khalikova Malokhat; Bakhriddinovna, Rakhmonova Rukhsora; Umrbekovna, Matyakubova Elmira; Aktam, Nurmamatov; Tulkinovich, Sharipov Shukhrat (Research Focus International Scientific Journal, 2026)
The use of naturally colored cotton fiber, which eliminates the need for chemical dyes and reduces environmental pollution, is a requirement of modern sustainable textile production. However, fiber color is usually negatively correlated with fiber quality in cotton. The objective of this study was to determine the polymorphism of fiber quality and color traits in cotton varieties and F4 hybrid combinations using SSR markers. As a result, hybrid combinations with high fiber quality stability (107 and 135 bp) and improved coloration, associated with a pleiotropic locus on chromosome 7 (genome A), were identified. Markers BNL1604 and NAU1043 demonstrated high informativeness for genotype identification, making them promising tools for molecular tagging of breeding material and accelerated selection for fiber quality and color traits. The use of SSR markers BNL1604 and NAU1043 enabled the identification of allelic combinations associated with improved fiber properties. The F4 hybrids L-001 × 010444 and Bukhara-6 × 02408 are recommended for further breeding as donors of genes for high fiber quality. Marker-based identification confirmed the effectiveness of SSR technology for accelerating selection in cotton breeding programs. The results of this study have both scientific and practical significance for developing environmentally safe varieties of naturally colored cotton with improved fiber properties.